2022
DOI: 10.3390/ijms232113314
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of AMT and NRT Gene Family in Pecan (Carya illinoinensis) Seedlings Revealed a Preference for NH4+-N

Abstract: Nitrogen (N) is a major limiting factor for plant growth and crop production. The use of N fertilizer in forestry production is increasing each year, but the loss is substantial. Mastering the regulatory mechanisms of N uptake and transport is a key way to improve plant nitrogen use efficiency (NUE). However, this has rarely been studied in pecans. In this study, 10 AMT and 69 NRT gene family members were identified and systematically analyzed from the whole pecan genome using a bioinformatics approach, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…After the transformation of Agrobacterium tumefaciens GV3101-pCAMBIA 1301-PtrAMT1;6P into the Arabidopsis Col-0 ecotype, pure lines were screened and used for GUS staining. The results showed that, at the seedling stage, GUS was expressed mainly on the rootstock junction, cotyledon petioles, and the veins and mesophyll cells closely connected to the petioles, but not in the roots or the newly emerged leaves, whereas the AMT gene was expressed mainly in the roots of Carya illinoinensis, probably because PtrAMT1;6 is a gene that controls the ammonium recycling function in the aboveground parts [25]. Although Arabidopsis and poplar are far apart in morphological structure, the expression activity of the PtrAMT1;6 promoter in Arabidopsis is not fully indicative of its expression activity in P. trichocarpa, but this result suggests that the PtrAMT1;6 promoter has promoter activity.…”
Section: Discussionmentioning
confidence: 98%
“…After the transformation of Agrobacterium tumefaciens GV3101-pCAMBIA 1301-PtrAMT1;6P into the Arabidopsis Col-0 ecotype, pure lines were screened and used for GUS staining. The results showed that, at the seedling stage, GUS was expressed mainly on the rootstock junction, cotyledon petioles, and the veins and mesophyll cells closely connected to the petioles, but not in the roots or the newly emerged leaves, whereas the AMT gene was expressed mainly in the roots of Carya illinoinensis, probably because PtrAMT1;6 is a gene that controls the ammonium recycling function in the aboveground parts [25]. Although Arabidopsis and poplar are far apart in morphological structure, the expression activity of the PtrAMT1;6 promoter in Arabidopsis is not fully indicative of its expression activity in P. trichocarpa, but this result suggests that the PtrAMT1;6 promoter has promoter activity.…”
Section: Discussionmentioning
confidence: 98%
“…We performed a genome-wide analysis to identify 12 AMT family genes that belong to two subfamilies in sweet potato. The phylogenetic analyses of the AMT proteins among sweet potato, Arabidopsis, rice, tomato, cassava, soybean, and maize AMT proteins indicated that the AMT of the studied species can be divided into three groups according to homology [48]. Furthermore, IbAMT1.3, AtAMT1.1, and SlAMT1.1 are homologous, and IbAMT1.5 shows a close relationship with AtAMT1.2 and SlAMT1.2.…”
Section: Relationship Between Amt Gene Family and N Uptake And Utiliz...mentioning
confidence: 91%
“…NRT1, NRT2, and NRT3 have different structural conformations (Figure 1). As a result, the Pfam database collects these genes under distinct families: PF00854 for NRT1, PF07690 for NRT2, and PF16974 for NRT3 [64]. PF00854 refers to the proton-dependent oligopeptide transporter (POT) family (also known as the peptide transporter (PTR) family) and is a class of energy-dependent transporters discovered in organisms ranging from bacteria to humans [65].…”
Section: Plant Nitrate Transportersmentioning
confidence: 99%